The Effect of Self-Concept and Learning Interest on Science Learning Achievement among Madrasah Tsanawiyah Students: Pengaruh Konsep Diri dan Minat Belajar terhadap Prestasi Belajar IPA Siswa Madrasah Tsanawiyah - Sumantri, Hendra; Rahman, Novianti Azizah (CV. Media Publikasi Profesional, 2025)
Self-concept and learning interest are important psychological factors that contribute to students' academic success, particularly in science subjects. This study aims to examine the influence of self-concept and learning interest on the science learning achievement of Madrasah Tsanawiyah students. The method used was a survey with correlation analysis and multiple linear regression techniques. The research population consisted of 500 students from three public Madrasah Tsanawiyah in Majalengka Regency, with a sample size of 89 students. The sampling technique used was stratified random sampling. The instruments employed were a self-concept questionnaire and a learning interest questionnaire. The results of the study showed that self-concept and learning interest significantly influence students’ science achievement. These findings highlight the crucial role of teachers in shaping positive self-concept and increasing students’ interest in learning to create an effective and enjoyable science learning environment. Academically, this study contributes to strengthening the educational literature that emphasizes the importance of affective factors such as self-concept and learning interest in supporting students’ academic success, and provides a foundation for the development of more comprehensive, character-oriented educational policies and interventions.